2014
DOI: 10.1039/c3nr04022d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticle-based substrates for cell directed delivery of Notch signalling modulators to control myoblast differentiation

Abstract: Biochemical cues are critical to control stem cell function and can be utilized to develop smart biomaterials for stem cell engineering. The challenge is to deliver these cues in a restricted manner with spatial and temporal control. Here we have developed bilayer films of mesoporous silica nanoparticles for delayed cellular delivery of Notch modulators to promote muscle stem cell differentiation. We demonstrate that drug-loaded particles are internalized from the particle-covered surface, which allows for dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 51 publications
2
43
1
1
Order By: Relevance
“…Below the toxic threshold, silica nanoparticles show potential development in biomedical research for bioimaging, diagnosis, drug delivery, and tissue engineering, including muscle regeneration therapy. 20,39,40 We have studied the internalization of silica NPs in myoblasts and characterized their biopersistence during in vitro cell differentiation, representing an excellent model for muscle regeneration. Interestingly, we showed that at low doses, NP uptake was able to increase the formation of myotubes by enhancing myoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Below the toxic threshold, silica nanoparticles show potential development in biomedical research for bioimaging, diagnosis, drug delivery, and tissue engineering, including muscle regeneration therapy. 20,39,40 We have studied the internalization of silica NPs in myoblasts and characterized their biopersistence during in vitro cell differentiation, representing an excellent model for muscle regeneration. Interestingly, we showed that at low doses, NP uptake was able to increase the formation of myotubes by enhancing myoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the differentiation of myoblasts has been stimulated with the use of silica nanoparticles loaded with γ-secretase inhibitors, blocking the Notch signaling pathway. 20 Developments combining stem cells with nanoparticles provide an interesting strategy for cell therapy. 21 Because muscles are scarcely exposed to nanoparticles, little attention has been given to how silica nanoparticles interact with muscle cells, unlike exposed tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have produced interesting advances in the use of silica materials for nanomedicine applications [29,[32][33][34]67,68]. Among several reviews the themed A c c e p t e d M a n u s c r i p t 10 features and applications are revised is worth citing [69].…”
Section: Ordered Mesoporous Silica Materialsmentioning
confidence: 97%
“…Particularly, we can cite the huge contribution of Vallet-Regì et al [18,[26][27][28][29][30], and more recently the careful work of Linden et al [31][32][33]. OMS materials are able to adsorb, protect and release therapeutic proteins and peptides, being the aim the preparation of drug depot systems for sustained drug delivery or bone tissue engineering [17,18].…”
Section: Introductionmentioning
confidence: 98%